Playing with the Goddess: Gavri of the Mewar Bhils - Mehta, Aditi Ghosh (New Delhi Indira Gandhi National Center for the Arts, 2024)
Aditi Ghosh Mehta joined the Rajasthan cadre of the Indian Administrative Service (IAS) in 1979. Brought up in a Bengali cultural milieu, she was largely educated in New Delhi and the United States. Encountering a Bhil Gavri performance during her first posting in 1981, she was struck by the enduring energy of Rajasthani folk and tribal cultural forms. As Director of the West Zone Cultural Centre, and in related institutional positions, she devoted herself to supporting the sustenance and growth of these forms, and engaging with issues of livelihoods, ecology, and development in the lives of tribals, nomadic communities, and de- notified tribals. This book has its roots in a four-decade long companionship with the Bhil Gavri form. It explores how amidst increasing marginalization, poverty and ecological destruction, ordinary people may continue to experience and create beauty through performance, art, and collective ritual life. Even as forms of tribal dispossession worsen, and the Gavri further transforms in the future, this three-volume work hopes to offer a way of accessing this inheritance, particularly for hose interested in the vitality of performance forms, and for future generations of Bhils.
Keywords: Art and Archaeology/Temples Add to Cart; Religion; Economic